USM RECEIVES COURTESY VISIT FROM THE ASSOCIATION OF PRIVATE UNIVERSITIES OF JAPAN - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 27 February 2017 Universiti Sains Malaysia (USM) ViceChancellor, Professor Datuk Dr. Asma Ismail today hosted a courtesy visit between USM and delegates from the Association of Private Universities of Japan at the Chancellory Conference Room, Chancellory Building here.